The effectiveness of the formulation of botanical insecticide marigold (Tithonia diversifolia) on Empoasca flavescens, a main pest on tea plant - Odih Sucherman (Jurnal Penelitian Teh dan Kina, 2012)
A research to know the effectiveness of formulation of botanical insecticide marigold (Tithonia diversifolia) on E. flavescens has been carried out at a green house of Research Institute for Tea and Cinchona (RITC), as well as at Pasir Sarongge Experimental Garden of RITC, Cianjur, West Java, from September up to November 2011. At both experimental sites, the experimentations was designed in a randomized complete block (RCB) withÂ  six treatments, replicated four times. Treatments tested were formulation of marigold extract 10% and 15%, each at doses of 0.5 and 1.0 l/ha, standard chemical insecticide, and control. All treatments were applied by spraying, using one litre-hand sprayer at green house, and using knapsack sprayer with spraying volume 300 l/ha in feld. At green house, parameter observed was mortality of E. flavescens. Mortality at formulation of marigold extract 15% (92%, in average) was higher than at formulation of marigold extract 10% (76%, in average) while in field were attack intensity of E. flavescens, tea shoot production, and phytotoxicity. Results showed that at green house, formulation of marigold extract 10% and 15% at doses of 0.5 dan 1.0 l/ha were effective to result in high mortality of E. flavescens. While in field the formulations at both doses were effective to suppress attack intensity of E. flavescens. However, the effectiveness of 1.0 l/ha doses was higher than 0.5 l/ha doses, which comparable with standard chemical insectiside treatment. The formulations at both doses indirectly also could increase shoot production, and did not cause phytotoxicityÂ  on tea leaves/shoots.